Development of a real-time duplex PCR assay for simultaneously diagnosis of KHV and CEV in common carp and koi - Khumaira Puspasari; Adityawati Fajar Rini; Noviana Dewi; Ratih Ismayasari (Jurnal Akuakultur Indonesia, 2023)
Koi herpesvirus (KHV) and carp edema virus (CEV) are potential risks for the koi trade and for global common carp aquaculture. Due to the severe impact of both viruses, a robust diagnostic tool was required, capable of detecting and distinguishing both infections with high accuracy and precision. The aim of this study was to describe a real-time duplex TaqMan PCR assay for simultaneous detection of KHV and CEV in common carp and koi. Two pairs of primers with two TaqMan probes were used to amplify specific and conserved regions of KHV and CEV DNA. This assay was confirmed to be sensitive and specific. Limit of detections of the assay were 15 DNA copies/µL for KHV and 150 DNA copies/µL for CEV, respectively. This assay was able to identify and distinguish CEV and KHV, but was unable to identify other pathogens and sample matrices. For clinical validation, 18 KHV and CEV positive samples each, as well as 12 negative samples were tested with three different test methods, i.e., real-time duplex PCR, real-time simplex PCR, and conventional PCR. All three tests provide optimal conformity of results. The results showed that real-time duplex PCR was able to detect the presence and distinguish each pathogen in infected fish. This real-time duplex PCR assay is a rapid, sensitive, and specific test for detecting KHV and CEV in carp fish, thus it can be considered a valid alternative assay in aquaculture clinical laboratories. Keywords: Cyprinus carpio, CEV, diagnostic, KHV, real-time duplex PCR ABSTRAK Koi herpesvirus (KHV) dan carp edema virus (CEV) merupakan risiko potensial untuk perdagangan koi dan budidaya ikan mas global. Karena dampak dari keduanya yang parah, maka diperlukan perangkat diagnostik yang tangguh, yang mampu mendeteksi dan membedakan keduanya dengan akurasi dan presisi yang tinggi. Tujuan dari penelitian ini adalah menjabarkan pengujian real time TaqMan PCR dupleks untuk mendeteksi KHV dan CEV pada ikan mas dan koi secara simultan dalam satu reaksi. Dua pasang primer dengan dua TaqMan probe digunakan untuk mengamplifikasi wilayah spesifik dan lestari dari DNA KHV dan CEV. Pengujian ini terbukti sensitif dan spesifik. Sensitivitas dari pengujian ini adalah 15 kopi DNA/µL untuk KHV dan 150 kopi DNA/µL untuk CEV. Pengujian ini mampu mengidentifikasi dan membedakan CEV dan KHV, tetapi tidak dapat mengidentifikasi patogen lain dan matriks sampel. Untuk validasi klinis, masing-masing 18 sampel positif KHV dan CEV, serta 12 sampel negatif diuji dengan tiga metode pengujian yang berbeda, yaitu real-time PCR dupleks, real-time PCR tunggal dan PCR konvensional. Ketiga pengujian tersebut memberikan kesesuaian hasil yang optimal. Hasil penelitian menunjukkan bahwa real-time PCR dupleks mampu mendeteksi keberadaan dan membedakan setiap patogen pada ikan yang terinfeksi. Uji real-time PCR dupleks ini merupakan pengujian yang cepat, sensitif, dan spesifik untuk mendeteksi KHV dan CEV pada ikan koi dan mas, sehingga dapat dipertimbangkan sebagai pengujian alternatif yang valid di laboratorium klinis akuakultur. Kata kunci: Cyprinus carpio, CEV, diagnostik, KHV, real-time PCR dupleks